073WS Collaborative Guideline Implementability Tool Development and Evaluation. (15th August 2013) - Cheng, J; Gagliardi, A; Melissa, B; Bhattacharyya, O
Abstract : Background: Research shows that guidelines are more easily translated to practice when accompanied by information that helps users accommodate, implement and evaluate use of the recommendations. We refer to this information in guidelines or other resources as guideline implementability tools (GItools). We identified exemplar GItools, generated criteria by which to assess and develop GItools through consultation with G-I-N members, and created an online directory for sharing of GItools. Discussion with G-I-N members would help us improve these resources and identify partners for collaborative GItool development. This work is a core activity of GIRAnet: the Guideline Implementability Research and Application Network (http://www.g-i-n.net/activities/implementation/giranet ). Objectives: To share information about GItool resources; gather feedback on how to improve GItool resources; learn about other GItool initiatives; and establish partners for joint development or evaluation of GItools. AUDIENCE Guideline developers, implementers, users (clinicians, managers, policy-makers) and researchers. Description: A brief presentation will define GItools and describe their potential purpose and impact; review methods used to identify, describe and evaluate exemplar GItools; and demonstrate the GItool Directory (20 minutes). Participants will be asked to individually rate, then discuss enhancements for GItool assessment criteria (20 min). Open discussion will enable sharing and mutual learning about other GItool initiatives, and explore partnerships for future GItool initiatives (40 min). Remaining time will be used to identify priorities for ongoing research (10 min). Participant feedback will be used to improve GItool resources, and guide ongoing GIRAnet projects.